Pelatihan Pembuatan Ecoprint oleh Mahasiswa Kampus Mengajar Angkatan 6 di SMKS Darul Falah Pagutan - Rahmatin, Johana Aulina; Agustina, Agustina; Jumatre, Jumatre (Rengganis Jurnal Pengabdian Masyarakat, 2024)
Ecoprint-making training by students from Kampus Mengajar 6 at Darul Falah Pagutan Vocational School to increase students' creativity and give appreciation for the results of students' work which is integrated with the Strengthening Pancasila Student Profile (P5) Project in project expo festival activities. This training was carried out through literature studies and the implementation of socialization, training, and mentoring, as well as the implementation of project expo festivals. The activity of making eco prints by 6 teaching campus students at Darul Falah Vocational School received a very good response from the school community. This indicates that this activity is very good to follow up on because it can increase students' motivation in honing their creativity and students also feel appreciated for the work they have created